The phylogenetic relationship and demographic history of rhesus macaques (Macaca mulatta) in subtropical and temperate regions, China - Yanyan Zhou; Jundong Tian; Mengya Han; Jiqi Lu (Ecology and Evolution, 2024)
Abstract Pleistocene climatic oscillations exerted significant influences on the genetic structure and demography of rhesus macaque (Macaca mulatta) in eastern China. However, the evolutionary history of rhesus macaques in subtropical and temperate China remained unclear and/or controversial. Herein, we analyzed the autosomes, mitochondrial genomes, and Y‐chromosomes from 84 individuals of Chinese rhesus macaque. The results revealed that (1) all individuals were clustered into pan‐west and pan‐east genetic groups, which exhibited Shaanxi Province as the northernmost region of western dispersal route of rhesus macaques in China; (2) in subtropical and temperate China, rhesus macaques were divided into four lineages (TH, DB, HS, and QL), and their divergence times corresponded to the Penultimate Glaciation (300–130 kya) and Last Glaciation (70–10 kya), respectively; (3) the individuals from Mt. Taihangshan (TH) are closely related to individuals from Mt. Dabashan (DB) in the autosomal tree, rather than individuals from Mt. Huangshan (HS) as indicated by the mitogenome tree, which supports the hypothesis that the ancestral rhesus macaques radiated into Mt. Taihangshan from Mt. Huangshan via Mt. Dabashan; and (4) the demographic scenario of the four lineages showed the ancestral rhesus macaques bottleneck and expansion corresponding to the suitable habitat reduction and expansion, which confirmed they had experienced northward recolonization and southward retreat events from Mt. Huangshan area via Northern China Plain to Northernmost China along with Pleistocene glacial cycles. This study provides a new insight into understanding how Pleistocene glaciation has influenced faunal diversity in subtropical and temperate China, especially for those exhibiting differential patterns of sex dispersal.